Alveolar osseous defect in rat for cell therapy. Preliminary report - Raposo-Amaral, Cassio Eduardo; Kobayashi, Gerson Shigeru; Almeida, Ana Beatriz; Bueno, Daniela F.; Freitas, Fatima Rodrigues de Souza E.; Vulcano, Luiz Carlos [UNESP]; Passos-Bueno, Maria Rita; Alonso, Nivaldo (Acta Cirúrgica Brasileira, 2010)
Purpose: To study were to reproduce an alveolar bone defect model in Wistar rats to be used for testing the efficacy of stem cell therapies. Additionally, we also aimed to determine the osteogenesis process of this osseous defect in the 1 month period post-surgery. Methods: The animals were randomly divided into two groups of 7 animals each. A gingivobuccal incision was made, and a bone defect of 28 mm(2) of area was performed in the alveolar region. Animals were killed at 2 weeks after surgery (n=7) and 4 weeks after surgery (n=7). Results: The average area of the alveolar defect at time point of 2 weeks was 22.27 +/- 1.31 mm(2) and the average area of alveolar defect at time point of 4 weeks was 9.03 +/- 1.17 mm(2). The average amount of bone formation at time point of 2 weeks was 5.73 +/- 1.31 mm(2) and the average amount of bone formation at time point of 4 weeks was 19 +/- 1.17 mm(2). Statistically significant differences between the amount of bone formation at 2 weeks and 4 weeks after surgery were seen (p=0.003). Conclusion: The highest rate of ossification occurred mostly from 2 to 4 weeks after surgery. This observation suggests that 4 weeks after the bone defect creation should be a satisfactory timing to assess the potential of bone inductive stem cells to accelerate bone regeneration in Wistar rats.

OBJETIVO: Reproduzir um novo modelo de defeito ósseo alveolar em ratos Wistar que será utilizado para terapia genética e estudos com células tronco. Adicionalmente, outro objetivo do presente estudo foi determinar o pico de regeneração óssea do defeito criado na região alveolar do modelo experimental. MÉTODOS: Os animais foram aleatoriamente divididos em dois grupos de sete animais. Através de uma incisão gengivobucal foi criado um defeito ósseo medindo 28 mm2 de área na região alveolar dos ratos. Os ratos foram sacrificados após duas semanas (n=7) e quatro semanas (n=7) da cirurgia. RESULTADOS: A área média do defeito alveolar após duas semanas de cirurgia foi de 22.27 ± 1.31 mm2 e a área média do defeito alveolar após quatro semanas de cirurgia foi de 9.03 ± 1.17 mm2. A taxa de formação óssea foi de 5.73 ± 1.31 mm2 após duas semanas de cirurgia e de 19 ± 1.17 mm2 após quatro semanas de cirurgia. Foi observada diferença estatisticamente significante na taxa de formação óssea entre o grupo dos animais sacrificados com duas e quatro semanas (p=0.003). CONCLUSÃO: Este estudo demonstrou que a maior taxa de regeneração óssea ocorreu no período entre duas e quatro semanas após a cirurgia de criação do defeito ósseo alveolar, portanto esta observação sugere que o período de tempo de quatro semanas será suficiente para avaliar a capacidade de células tronco em regenerar osso em ratos Wistar com defeito ósseo alveolar.
Defeito ósseo alveolar em ratos para terapia celular. Estudo preliminar
Keywords: Alveolar Bone Loss; Tissue Therapy; Rats